Analisis Pengembangan Strategi Pemasaran Berbasis Pasar dalam Upaya Meningkatkan Kinerja Pemasaran Bank Sampah (Studi Kasus Bank Sampah Bersinar Kabupaten Bandung Jawa Barat) - Sri Sukartono; Eddy Jusuf; Juanim Juanim (Journal of Management and Bussines (JOMB), 2024)
This research explores various waste management models with a focus on Waste Banks as one solution to reduce waste problems. Conducted at the Bersinar Waste Bank, Bandung, this research was qualitative using the Exploratory Research method and snowball sampling interviews with leaders, employees and customers of the Bersinar Waste Bank as key informants. Adopting the 7P Marketing Strategy concept (Product, Price, Place, Promotion, People, Process, Physical Evidence) with the STP (Segmenting, Targeting, Positioning) approach by Philip Kotler and Keller (2016), this research also applies SWOT analysis to choose a marketing strategy right. The research results highlight strengths, weaknesses, opportunities and threats in the management and marketing aspects of Bank Sampah Bersinar, assisting in formulating effective marketing performance strategies through the SWOT matrix. Companies design policies based on weakness-opportunity (WO) strategy, strength-opportunity (SO) strategy, strength-threat (ST) strategy, and weakness-threat (WT) strategy. In conclusion, through intensive counseling to customers, including scavengers around the waste bank, it is hoped that it can increase awareness and participation in waste sorting, increase the added value of waste, as well as take advantage of opportunities and overcome threats faced by the Bersinar Waste Bank. Keywords: Waste Bank, Marketing Development, Marketing Strategy